Incidence and prevalence of antibody to hepatitis C virus in FDNY first responders before and after work at the World Trade Center disaster site. Issue 9 (20th June 2018) - Webber, Mayris P.; Liu, Yang; Cohen, Hillel W.; Schwartz, Theresa; Weiden, Michael D.; Kelly, Kerry; Ortiz, Viola; Zeig‐Owens, Rachel; Jaber, Nadia; Colbeth, Hilary L.; Prezant, David J.
Abstract : Background: The goals of this study were to assess the impact of work at the World Trade Center (WTC) site in relation to new, post‐9/11/2001 (9/11) antibody to hepatitis C Virus (anti‐HCV); and, evaluate secular trends in WTC‐exposed male Fire Department of New York City (FDNY) Firefighters and Emergency Medical Services (EMS) responders. Methods: FDNY monitors responder health through physical exams and routine blood work. We used descriptive statistics to compare trans‐9/11 and post‐9/11 incidence and to assess trends in prevalence from 2000 to 2012. Results: Trans‐9/11 incidence of new anti‐HCV was 0.42 per 100 persons compared with post‐9/11 incidence of 0.34 ( P = 0.68). Overall seroprevalence was 1.3%; rates declined from 1.79 per 100 to 0.49 per 100 over time ( P < 0.0001). Conclusions: Work at the WTC was not associated with new infection. Biennial seroprevalence in responders declined over time, supporting the FDNY decision to discontinue routine annual testing in this cohort.